ANALISIS IMPLEMENTASI 7 KEBIASAAN ANAK HEBAT DALAM PEMBENTUKAN KARAKTER POSITIF SISWA KELAS 3 SEKOLAH DASAR - Imamatul Khusna, Siti Nur; Sumartiningsih, Sri; Avrillianda, Decky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the contribution of the “7 Habits of Great Indonesian Children” program in shaping positive character values among elementary school students. The research employed a literature review approach by analyzing 15 national scientific articles published between 2021 and 2025. The review focused on synthesizing empirical and theoretical findings related to the implementation of positive habits in both school and family environments. The results indicate that the seven key habits waking up early, worshiping, exercising, eating healthy, enjoying learning, engaging with the community, and sleeping early are proven effective in developing students’ discipline, responsibility, religiosity, and social awareness. The success of the program is largely determined by teachers’ role modeling, parental involvement, and a supportive school culture that continuously reinforces positive behavior. However, several challenges remain, including excessive gadget use, inconsistent implementation at home, and limited character monitoring outside of school. Therefore, a strong collaboration between schools, families, and communities is essential to ensure the sustainability and effectiveness of the program. Overall, the findings highlight that the 7 Habits of Great Indonesian Children Movement serves as a relevant and practical strategy for character education that aligns with the vision of the Profil Pelajar Pancasila (Pancasila Student Profile) fostering learners who are faithful, independent, disciplined, and morally upright.